Ferroelectric and antiferrodistortive phase transition in the multiferroic (Bi0.8Ba0.2)(Fe0.8Ti0.2)O 3: A high temperature neutron powder diffraction study - Singh A.; Senyshyn A.; Fuess H.; Pandey D. (My University, 2025)
Presented here are the results of Rietveld analysis of powder neutron diffraction data, which reveal that both the ferroelectric and antiferrodistortive phase transitions occur together at T ∼ 925 K during heating, leading to a change in crystal structure from room temperature rhombohedral phase in the R3c space group with tilted oxygen octahedra to the high temperature paraelectric and paraelastic cubic phase in Pm3̄m space group. The presence of superlattice peaks due to antiphase rotation of oxygen octahedra in the rhombohedral phase until the transition to the cubic phase precludes the possibility of an intermediate R3m space group, conjectured previously on the basis of an x-ray powder diffraction study. Discontinuous change in the unit-cell volume, tilt angle, and bond lengths at the transition temperature TC, and phase coexistence of R3c and Pm3̄m over 100 K range across TC, suggest that the transition is of first order. It is argued that the R3c to Pm3̄m phase transition is of trigger type involving simultaneous condensation of Γ4- and R4+ modes. © 2011 American Institute of Physics.